2016
DOI: 10.1080/00016489.2016.1221132
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic value of measurement of cochlear length and height in temporal bone CT multiplanar reconstruction of inner ear malformation

Abstract: The normal range values of inner ear radial lines were measured and formulated, of which CL was 8.1-9.59 mm and CH was 3.28-3.90 mm. According to inner ear morphology and the normal values measured above, 61 cases of incomplete partition-type II (IP-II) and a high percentage (27/110, 24.5%) of hypoplasia of cochlea (HC) were diagnosed. The HC group was further divided into 1-turn, 1.5-turn, and 2-turn sub-groups, which had CDL of 15.98 ± 1.48 mm, 21.36 ± 0.96 mm, and 26.56 ± 0.60 mm, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 18 publications
5
37
3
Order By: Relevance
“…A comparison of the results of the left and right sides revealed that the difference between the two sides was not statistically significant. Also, compared with the results, obtained from a HRCT image, reported by Liu et al (2016) the results of this study were slightly larger. Nevertheless, the measurement results in the 3D models used in this study were closer to the true value, and are consistent with the results reported by Shin et al (2013).…”
Section: Variation In the Size And Orientation Of The Human Cochleacontrasting
confidence: 65%
“…A comparison of the results of the left and right sides revealed that the difference between the two sides was not statistically significant. Also, compared with the results, obtained from a HRCT image, reported by Liu et al (2016) the results of this study were slightly larger. Nevertheless, the measurement results in the 3D models used in this study were closer to the true value, and are consistent with the results reported by Shin et al (2013).…”
Section: Variation In the Size And Orientation Of The Human Cochleacontrasting
confidence: 65%
“…Furthermore, dysplasia and other syndromes exist which have an effect on cochlear geometry, especially regarding the length, shape and number of turns (e.g. Mondini dysplasia) [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Majority agrees that measuring the basal turn diameter which is also called as “A” value of the cochlea (Fig. 1A) from the pre-operative CT image of the cochlea, is relevant in estimating the full length of the cochlear duct length 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21. Escude et al 4 and Erixon et al 5 have proposed mathematical equations that involve “A” value as the input in estimating the CDL (LW) position, whereas the equations proposed by Alexiades et al 8 and Koch et al 22 estimates the CDL (OC) position.…”
Section: Methodsmentioning
confidence: 87%